"Almost there": sonically controlled vibrators, sound, and emotions. (15th March 2019) - Anderson-Kunert, Todd
Abstract : Purpose: The purpose of this paper is to demonstrate how practice-led research within the sonic practice references what Smith and Dean (2009) describe as the "The Iterative Cyclic Web, " and oscillations between different modes of research and practice throughout the methodology. Design/methodology/approach: This paper uses this process to document the construction of a sonically based erotic artwork, "Almost there, " which used sonically controlled vibrators in order to generate vocal content. Findings: The paper found that it was important to oscillate between modes of research and practice in order to create a conceptually concise artwork that functioned as a Gestalt of both practice and research. Originality/value: The unique approach to audio collection within this sonic artwork, and the time taken to collect this source material, makes it a unique vehicle for the consideration of "The iterative Cyclic Web."